Trajectories of maternal depressive and anxiety symptoms and child's socio-emotional outcome during early childhood - Korja, Riikka (Elsevier, 2025)
Maternal symptoms of depression and anxiety during pregnancy and early postnatal years are suggested to impose differential negative effects on child's socio-emotional development depending on the characteristics of the symptoms, such as timing, intensity, and persistence. The aim of this study was to identify trajectories of maternal depressive and anxiety symptoms from pregnancy until 2 years postpartum and to examine their relationship with child socio-emotional problems and competence at 2 and 5 years of age. The sample included 1208 mother-infant dyads from FinnBrain Birth Cohort study. Latent growth mixture modelling (LGMM) was utilized to model the trajectories of maternal depressive symptoms, measured using the Edinburgh Postnatal Depression Scale (EPDS), and general anxiety, measured with Symptom Checklist-90 (SCL-90) at 14, 24, and 34 weeks' gestation (gw) and at 3, 6 and 24 months postpartum. Maternal depression was also assessed at 12 months. Child socio-emotional problems and competence were evaluated using the Brief Infant Toddler Social Emotional Assessment (BITSEA) at 2 years and Strengths and Difficulties Questionnaire (SDQ) at 5 years. Relevant background factors and maternal concurrent symptomatology were controlled for. The trajectories of maternal depressive and anxiety symptoms were associated negatively with differential aspects of child long term socio-emotional outcomes from early toddlerhood to preschool years. The trajectories of depressive symptoms and high-level persistent symptoms that continued from pregnancy to two years of child age had the strongest negative association with child outcomes. This highlights the importance of identifying and treating maternal symptomatology, especially that of depression, as early as possible.